Constraints on mantle viscosity and Laurentide ice sheet evolution from pluvial paleolake shorelines in the western United States: Datasets - Jacky Austermann; Christine Y. Chen; Harriet C.P. Lau; Adam C. Maloof; Konstantin Latychev (Zenodo, 2019)
***********Please view the README.txt file for detailed documentation of data. *********** Title: Constraints on mantle viscosity and Laurentide ice sheet evolution from pluvial paleolake shorelines in the western United States: Datasets Version: 1.0 Date of Release: 2019/12/16 Identifier: 10.5281/zenodo.3576251 Associated publication: Austermann, J., Chen, C.Y., Lau, H.C.P., Maloof, A.C., and Latychev, K. (2019) Constraints on mantle viscosity and Laurentide ice sheet evolution from pluvial paleolake shorelines in the western United States. Earth and Planetary Science Letters . doi:10.1016/j.epsl.2019.116006 Link to publication: https://doi.org/10.1016/j.epsl.2019.116006 Suggested citation: Please reference the associated publication above when using any datasets or materials described in the README file. Contact information: Jacky Austermann (jackya@ldeo.columbia.edu) andChristine Y. Chen (cychen.earth@gmail.com) --- This directory contains the following datasets: SHORELINE FEATURE ELEVATION DATA Bonneville_Provo_Sehoo_shoreline_feature_elev_Austermann2019_EPSL.xlsx : shoreline feature elevation measurements of the Bonneville,Provo, and Sehoo lake stages of Lake Bonneville and Lake Lahontan; original measurements were made by Adams et al. (1999),Chen and Maloof (2017), and Currey (1982) MODELED RECONSTRUCTIONS OF LAKE VOLUME AND PALEOTOPOGRAPHY LakeBonneville_NAICE_l20.ump02p25.lmp5VM5.mat: model output for Lake Bonneville, including reconstructions of lake volume and paleotopography LakeLahontan_NAICE_l20.ump02p25.lmp5VM5.mat :model output for Lake Lahontan, including reconstructions of lake volume and paleotopography